2019
DOI: 10.3390/jcm8091271
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Parameters as Predictors of Treatment Response to Eplerenone in Central Serous Chorioretinopathy

Abstract: Purpose: To present data on clinical response to eplerenone over a 1-year period in patients with central serous chorioretinopathy (CSC), and to evaluate optical coherence tomography (OCT) variables as predictors of treatment response at 3- and 12-month follow-up visits. Methods: Patients with acute or chronic CSC treated with eplerenone were retrospectively included. Clinical and imaging characteristics were recorded at baseline and at the 3-month and 12-month follow-up visits. Changes from baseline in quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…e presence of HRF has revealed prognostic and clinical implications in several retinal diseases [7][8][9][10][11][12] and has influenced the evaluation of treatment response in DME [13,14]. In particular, HRF have been hypothesized to represent microglial cells when responding to specific morphometric criteria visible on OCT B-scans.…”
Section: Introductionmentioning
confidence: 99%
“…e presence of HRF has revealed prognostic and clinical implications in several retinal diseases [7][8][9][10][11][12] and has influenced the evaluation of treatment response in DME [13,14]. In particular, HRF have been hypothesized to represent microglial cells when responding to specific morphometric criteria visible on OCT B-scans.…”
Section: Introductionmentioning
confidence: 99%
“…In a mouse transgenic model that overexpresses the human MR, we observed pathologic changes in the RPE/choroid that mimic the pachychoroid phenotype, without pathologic changes in the neural retina. These results indicate that chronic systemic dexamethasone treatment causes an overactivation of the MR pathway, specifically in the RPE/choroid complex and not in the retina [33,53,54].…”
Section: Discussionmentioning
confidence: 77%
“…NVC changes as an enlargement of capillaries, glomerular loops, meandering loops, ramified capillaries and neoangiogenesis correlated significantly with HF. Hyperreflective foci was previously described in CSC and was proposed as an independently significant predictor for macular SRF complete resolution at 3 months [12]. It was suggested that HF constitute the extravasation of lipoproteins or activated microglia with a phagocytized photoreceptor or intraretinally migrated RPE.…”
Section: Discussionmentioning
confidence: 86%